2014
DOI: 10.1242/dev.098954
|View full text |Cite
|
Sign up to set email alerts
|

Hox proteins drive cell segregation and non-autonomous apical remodelling during hindbrain segmentation

Abstract: Hox genes encode a conserved family of homeodomain transcription factors regulating development along the major body axis. During embryogenesis, Hox proteins are expressed in segment-specific patterns and control numerous different segment-specific cell fates. It has been unclear, however, whether Hox proteins drive the epithelial cell segregation mechanism that is thought to initiate the segmentation process. Here, we investigate the role of vertebrate Hox proteins during the partitioning of the developing hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 106 publications
1
18
0
Order By: Relevance
“…39 In mosaic experiments, forced expression of EphrinB2a, EphA4 or EphB4, caused cells to sort out from those segments where these molecules are normally not expressed and to integrate into the adjacent segments where they are expressed. 33,54,56 These results were mirror-imaged in loss-offunction experiments: depleted cells sorted from those rhombomeres that expressed this particular component (r3 and r5 for EphA4MO, r4 for ephrinB2a), but integrated the adjacent rhombomeres where it was naturally absent.…”
Section: Hindbrain Segmentationmentioning
confidence: 86%
See 1 more Smart Citation
“…39 In mosaic experiments, forced expression of EphrinB2a, EphA4 or EphB4, caused cells to sort out from those segments where these molecules are normally not expressed and to integrate into the adjacent segments where they are expressed. 33,54,56 These results were mirror-imaged in loss-offunction experiments: depleted cells sorted from those rhombomeres that expressed this particular component (r3 and r5 for EphA4MO, r4 for ephrinB2a), but integrated the adjacent rhombomeres where it was naturally absent.…”
Section: Hindbrain Segmentationmentioning
confidence: 86%
“…For instance, EphA4 expression in r3 and r5 depends on Krox20, EphA2 in r4 onHoxA1 and HoxB1, 53 while the continuous expression of EphA7 in most rhombomeres, but with a sharp r6/7 boundary, is due to repression by HoxB4/D4 in the more anterior segments. 54 Thus the overall pattern may be explained by the conjunction of activations and repressions controlled by the multiple HOX genes expressed in overlapping domains.…”
Section: Ephrin-eph Expression In the Gastrulamentioning
confidence: 99%
“…Zhou et al (51) indicated that Nkx3.1, a homeoprotein transcription factor, functions within the cells that produce them in a cell autonomous manner as well as can regulate genes and inhibit cell proliferation in a non-cell autonomous manner. Prin et al (52) reported that Hox4 proteins regulate Eph/ephrins and other cell-surface proteins during chick and mouse embryo development. These proteins can also function in a non-cell-autonomous manner to induce apical cell enlargement on both sides of their expression border.…”
Section: Discussionmentioning
confidence: 99%
“…Modulating cell shape is another way to control single or collective cell migration and tissue remodelling, and Hoxb1b has recently been shown to regulate microtubule dynamics during the process of neural tube formation in zebrafish (Zigman et al, 2014). Hox proteins also directly regulate cell shape, cell-to-cell communication and signalling to properly delimit functional and morphological borders between vertebrate hindbrain segments (Prin et al, 2014), and the Drosophila Hox protein Abdominal B (AbdB) has been shown to coordinate the modifications in cell adhesion and cytoskeleton required for cell shape changes and invagination during development of the posterior spiracle, which constitutes the posterior end of the larval respiratory system (Castelli Gair Hombria et al, 2009). Hox proteins can also couple differentiation with morphogenesis, controlling cell fate decisions along differentiation lineages.…”
Section: An Overview Of the Hox Gene Familymentioning
confidence: 99%